An antigen-specific immunotherapeutic, AKS-107, deletes insulin-specific B cells and prevents murine autoimmune diabetes - Alleva, David G.; Delpero, Andrea R.; Sathiyaseelan, Thillainaygam; Murikipudi, Sylaja; Lancaster, Thomas M.; Atkinson, Mark A.; Wasserfall, Clive H.; Yu, Liping; Ragupathy, Ramya; Bonami, Rachel H.; Zion, Todd C. (Frontiers in Immunology, 2024)
The antigen-presenting cell function of insulin-reactive B cells promotes type 1 diabetes (T1D) in non-obese diabetic (NOD) mice by stimulating pathogenic T cells leading to destruction of insulin-producing β-cells of pancreatic islets. To target insulin-reactive B cells, AKS-107, a human IgG1 Fc molecule fused with human insulin A and B chains, was engineered to retain conformational insulin epitopes that bound mouse and human B cell receptors but prevented binding to the insulin metabolic receptor. AKS-107 Fc-mediated deletion of insulin-reactive B cells was demonstrated via ex vivo and in vivo experiments with insulin-reactive B cell receptor transgenic mouse strains, VH125Tg/NOD and Tg125(H+L)/NOD. As an additional immune tolerance feature, the Y16A mutation of the insulin B(9-23) dominant T cell epitope was engineered into AKS-107 to suppress activation of a insulin-specific T cells. In mice and non-human primates, AKS-107 was well-tolerated, non-immunogenic, did not cause hypoglycemia even at high doses, and showed an expectedly protracted pharmacokinetic profile. AKS-107 reproducibly prevented spontaneous diabetes from developing in NOD and VH125Tg/NOD mice that persisted for months after cessation of treatment, demonstrating durable immune tolerance. These preclinical outcomes position AKS-107 for clinical development in T1D prevention settings.